Prevalence and antibiotic susceptibilities of pathogenic Yersinia enterocolitica strains in pigs slaughtered in northern Italy - Ossiprandi, Maria Cristina; Zerbini, Laura (JOURNAL OF ADVANCES IN BIOLOGY, 2014)
Yersinia enterocolitica is an important zoonotic pathogen causing yersiniosis in humans and animals. Human yersiniosis is the third most common enteric disease after campylobacteriosis and salmonellosis in many European countries. Yersinia enterocolitica strains, belonging to bioserotypes associated with human disease, have frequently been isolated from tonsils and faecal samples of domestic pigs. In this study, 46 of 354 tonsils from healthy slaughtered pigs resulted Yersinia spp.-positive (13.0%). The most common serotypes of Y. enterocolitca (42 strains) and Y. pseudotuberculosis (4 strains) were 4/O:3 (95.2%) and III, respectively. Antimicrobial susceptibility testing of the 42 Y. enterocolitica isolates showed that all strains were resistant to the beta-lactam antibiotics tested and to erythromycin and novobiocin, while 90.5% and 67.7% were resistant to nalidixic acid and rifampicin, respectively. High rates of resistance towards tetracycline (50%) and chloramphenicol (38.1%) were found, while low frequencies were observed to gentamicin (2.4%), kanamycin (11.9%) and neomycin (21.4%). One strain was resistant to all the antibiotics-tested. Our results confirm the pigs as an important reservoir of pathogenic Y. enterocolitica and demonstrate the existence of a progressive increase of multi-drug resistance.